Mechanical design of an automated vehicle driving system for drive cycle testing - Saini, Adam (2016)
This thesis describe the mechanical design process for an automated drive cycle testing system. Drive cycle is a graph containing series of vehicle speed data versus time. The main reason for drive cycle existence is to analyse the air pollution that is emitted by vehicle engines through combustion process. It is also can be used as a reference for vehicle manufacturer in order to design their engine, which may reduce the possibility of air pollution release to the air and also to reduce the fuel usage to reach higher distances travel per litre fuel. The mechanical design for automated drive cycle system is needed in order to eliminate human as a medium that will run the drive cycle test. The purpose for human driver elimination is due to susceptible human error, the inconsistency in driving pattern and also the need of training for the driver to run the drive cycle test. There are two objective for this project, which is to design a mechanism that can be used to control a passenger vehicle according to standard drive cycles and to adapt the mechanism with a separate closed-loop control system to enable transient speed-load testing of a vehicle. This objective will be done on a specific vehicle which is Perodua Myvi with automatic gear shifting. There are several findings that related to vehicle control which eliminate human as the handler. From the finding and the requirement to work on a small space area, the new concept for mechanical design is needed. The flow for design process that will be conducted is based on the Pahl and Beitz design method. Referring to the step in the design method, the step will go through several estimation and task specification such as defining task, conceptual design, embodiment design, analysis and detail design that will help in designing the product. The fabrication process give out many challenges and the idea to overcome the problem is describe in the thesis.